Improving the Quality of the Curriculum at the Integrated Tahfidzul Qur'an Elementary School in Banjarmasin City: Peningkatan Mutu Kurikulum Di Sekolah Dasar Tahfidzul Qur’an Terpadu Kota Banjarmasin - Mulyadi, Rida; Hermina, Dina; Sholeh, Makherus (Madrosatuna: Journal of Islamic Elementary School, 2024)
This research explored the quality improvement of elementary schools integrated at Tahfidzul Qur'an Elementary School (SDTQ-T) Irsyadul Aulad Banjarmasin. This research is conducted using a descriptive qualitative research method. The data were collected through interviews with the principals and teachers at SDTQ-T Irsyadul Aulad Banjarmasin about curriculum quality improvement. The results showed that the curriculum implementation process at SDTQ-T Irsyadul Aulad Banjarmasin is carried out by the curriculum planning process that has been determined. Then, the curriculum is developed according to student needs and school characteristics. However, sometimes, the lesson plans that have been made are not maximized during the learning process in the classroom. This will be a separate evaluation process for teachers to continue to improve the quality of their teaching in the school. Furthermore, SDTQ-T Irsyadul Aulad Banjarmasin teachers have realized concrete indicators of curriculum development competence. But it's just not too optimal.